2022
DOI: 10.3389/fphys.2022.1010069
|View full text |Cite
|
Sign up to set email alerts
|

Multiple rather than specific autoantibodies were identified in irritable bowel syndrome with HuProt™ proteome microarray

Abstract: Immune activation and several autoantibodies might be involved in the pathophysiology of irritable bowel syndrome (IBS). We aimed to identify serum biomarkers for IBS by HuProt™ microarray. IBS patients met Rome III criteria were enrolled. Control groups included healthy controls (HCs) and disease controls (DCs). In stage I, we profiled sera from IBS and control groups with HuProt™ microarrays. Based on significant different proteins in stage I, IBS focused microarrays were constructed and validated in a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Vasapolli et al demonstrated that both the antibody and gut microbial profiles failed to discriminate between IBS and other functional gastrointestinal disorder subgroups ( Vasapolli et al, 2021 ). We conducted a large cohort study using HuProt™ microarrays and reported that five autoantibodies of IgG and seven IgA were comprehensively involved in differentiating IBS patients from healthy controls with a sensitivity and specificity of 40%–46.7% and 79.4%–86.3%, respectively; however, no specific autoantibodies could serve as serum biomarkers for IBS ( Fan et al, 2022 ).…”
Section: Autoantibodies As Biomarkers Of Ibsmentioning
confidence: 99%
“…Vasapolli et al demonstrated that both the antibody and gut microbial profiles failed to discriminate between IBS and other functional gastrointestinal disorder subgroups ( Vasapolli et al, 2021 ). We conducted a large cohort study using HuProt™ microarrays and reported that five autoantibodies of IgG and seven IgA were comprehensively involved in differentiating IBS patients from healthy controls with a sensitivity and specificity of 40%–46.7% and 79.4%–86.3%, respectively; however, no specific autoantibodies could serve as serum biomarkers for IBS ( Fan et al, 2022 ).…”
Section: Autoantibodies As Biomarkers Of Ibsmentioning
confidence: 99%